2019
DOI: 10.1111/den.13528
|View full text |Cite
|
Sign up to set email alerts
|

Underwater endoscopic mucosal resection for complete R0 removal of an adenoma extending into the appendiceal orifice

Abstract: Watch a video of this article

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Furthermore, submucosal scarring after previously attempted endoscopic removal significantly reduces the efficacy of submucosal injection. Underwater endoscopic mucosal resection (UEMR) can be effective for poorly visualized polyps, such as orifice- or diverticular-related polyps, or for scarred residual polyps 2 3 4 . Nevertheless, suboptimal visualization of the proximal margins in the deflated lumen hampers effective snaring.…”
Section: Figmentioning
confidence: 99%
“…Furthermore, submucosal scarring after previously attempted endoscopic removal significantly reduces the efficacy of submucosal injection. Underwater endoscopic mucosal resection (UEMR) can be effective for poorly visualized polyps, such as orifice- or diverticular-related polyps, or for scarred residual polyps 2 3 4 . Nevertheless, suboptimal visualization of the proximal margins in the deflated lumen hampers effective snaring.…”
Section: Figmentioning
confidence: 99%
“…Two case reports showed successful resection with UEMR for complete removal of adenoma with extension into an appendiceal orifice. 37 , 38 Furthermore, a prospective study on clinical outcomes of UEMR for lesions involving an appendiceal orifice found that UEMR was successful in 89% (24/27) with the post‐polypectomy syndrome in 7% and local recurrence rate of 10%. 39 Three case reports indicated complete removal of adenoma extending into a colonic diverticulum or surrounded by a diverticulum using UEMR.…”
Section: Uemr In Case Reports Under Special Situationsmentioning
confidence: 99%
“…UEMR was described as being useful in case reports under special situations. Two case reports showed successful resection with UEMR for complete removal of adenoma with extension into an appendiceal orifice 37,38 . Furthermore, a prospective study on clinical outcomes of UEMR for lesions involving an appendiceal orifice found that UEMR was successful in 89% (24/27) with the post‐polypectomy syndrome in 7% and local recurrence rate of 10% 39 .…”
Section: Uemr In Case Reports Under Special Situationsmentioning
confidence: 99%